Community Aspirations for Landscape Management in Kongwa District, Tanzania - Desta, Gizaw; Dulazi, Ashura Alley; Swai, Elirehema (International Crops Research Institute for the Semi-Arid Tropics, 2024)
This briefing paper outlines the aspirations of communities in Kongwa District, Tanzania, for effective landscape management. Forty-seven farmers (14 of them were women) from eight villages discussed the contextual characteristics of farms and landscapes, identifying key challenges and underscoring the importance of enforcing community-agreed bylaws and promoting sustainable practices. The paper details the community’s vision for technological, technical, and institutional improvements to achieve desirable landscape changes. It calls for coordinated efforts among community institutions, village governments, and experts to develop practical action plans and harmonized landscape management strategies.